Diversity of methicillin-resistant staphylococci among wild Lepus granatensis: first detection of mecA-MRSA in hares. Issue 1 (19th December 2019) - Silva, Vanessa; Pereira, José Eduardo; Maltez, Luís; Ferreira, Eugénia; Manageiro, Vera; Caniça, Manuela; Capelo, José L; Igrejas, Gilberto; Poeta, Patrícia
ABSTRACT: MRSA in humans, pets and livestock have been widely investigated, nevertheless, there is still little information of MRSA in wild animals. Therefore, this study aimed to investigate the occurrence and antimicrobial resistance profiles of methicillin-resistant staphylococci (MRS) in wild Iberian hares and to characterize their genetic lineages. Samples from 83 wild hares ( Lepus granatensis ) were collected during the hunting season. Isolation of MRS was accomplish using Oxacillin Resistant Screening Agar medium with 2 mg/L of oxacillin. The susceptibility of the isolates was tested by the Kirby-Bauer disc diffusion method. The presence of resistance and virulence genes was studied by PCR. S. aureus strains were further characterized by multilocus sequence typing, agr, spa and SCC mec typing. From the 83 samples, 12 (14.45%) coagulase-negative staphylococci and 3 (3.6%) MRSA strains were isolated. Nine coagulase-negative isolates showed resistance to at least one antibiotic. One MRSA isolate showed a multidrug-resistant profile with resistances to ß-lactams, aminoglycosides, macrolides and lincosamides. All MRSA strains were ascribed to ST2855, t1190 and SCC mec type III. The frequency of MRSA strains in wild hares was low, nevertheless, the presence of MRSA in game animals is considered a public health problem and may represent a route of transmission between animals and humans. Abstract : First reported description of the presence of mecA-MRSA among wild hares and diversity of other methicillin-resistant staphylococci in wild hares.